2011
DOI: 10.2202/2154-3348.1025
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Nonprofit Organizations and the Fight for Comprehensive Immigration Reform

Abstract: , including over seventy interviews of nonprofit, public, and private sector leaders, this paper explores how immigrant nonprofit organizations participated in the one-year lifecycle of the Reform Immigration for America (RI4A) campaign in Philadelphia. Furthermore, the paper analyzes the institutional legacy the campaign left on these organizations, as they continue to promote immigrant integration and engage in political advocacy at the local level. Finally, the paper shares lessons learned from the Philadel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Despite its apparent importance, there is scant research focused on the incorporation of social media for nonprofits that serve the political and civic needs of immigrants. Wilson (2011) addressed immigrant-serving nonprofit organizations and immigration policy debates but included little on communication tactics. And Andersen (2010) showed that few immigrant-serving nonprofit organizations pursued voter engagement, but she did not focus on social media.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Despite its apparent importance, there is scant research focused on the incorporation of social media for nonprofits that serve the political and civic needs of immigrants. Wilson (2011) addressed immigrant-serving nonprofit organizations and immigration policy debates but included little on communication tactics. And Andersen (2010) showed that few immigrant-serving nonprofit organizations pursued voter engagement, but she did not focus on social media.…”
Section: Conceptual Frameworkmentioning
confidence: 99%